Exploring the mediating role of flexible working hours in the relationship of supervisor support, job and life satisfaction: A study of female nurses in China - Oscar Dousin; Chen Xi Wei; Bamini K. P. D. Balakrishnan; Michelle Chin Chin Lee (Wiley, 2021)
Abstract Aims To examine the mediating role of flexible working hours on the relationship between supervisor support, job and life satisfaction among female nurses in China. Design A cross‐sectional, quantitative study was conducted with online survey questionnaires. Methods Convenience sampling was implemented with 171 female nurses from two tertiary public hospitals in 2019. Results The mediation analysis demonstrates that flexible working hours significantly and positively mediate the relationship between supervisor support to job (β = 0.775, p < .001) and life satisfaction (β = 0.745, p < .001). In addition, supervisor support and flexible working hours significantly and positively influence job (r = 0.520, p < .01; r = 0.520, p < .01) and life satisfaction (r = 0.487, p < .01; r = 0.487, p < .01). The study suggested that flexible working hours iarean indicator of what supervisor support (r = 0.656, p < .01) is to improve nurses' job and life satisfaction. The study revealed that flexible working hours and supervisor support are crucial to female nurses who face high demands at both work and home.